Development of g-C3N4/BiVO4 Binary Component Heterojunction as an Advanced Visible Light-Responded Photocatalyst for Polluted Antibiotics Degradation - Nguyen Le Minh Tri; Nguyen Thi Dieu Cam; Hai Dinh Pham; Doan Van Thuan; Thanh-Dong Pham; Van Tang Nguyen; Nguyen Tien Trung; Mai Hung Thanh Tung; Tran Thi Thu Phuong; Thi Thu Phuong Nguyen; Cao Van Hoang; Van Duong Dao (My University, 2021)
Development of g-C3N4/BiVO4 Binary Component Heterojunction as an Advanced Visible Light-Responded Photocatalyst for Polluted Antibiotics Degradation
Keywords: Heterojunction g-C3N4/BiVO4; Quang xúc tác; Kháng sinh tồn dư